Quality Control of HDL: Nutrition and Not Numbers May Determine HDL Functionality - Nathalie Nicod,; Francesco Visioli,; Ana Ramírez de Molina Madrid, (Journal of Pharmacy and Nutrition Sciences, 2011)
The strong inverse relationship between high density lipoproteins-cholesterol (HDL-C) levels and cardiovascular disease (CVD) has aroused a strong interest in the research of lifestyle and pharmacological agents capable of elevating plasma HDL levels. HDL is essential in reverse cholesterol transport (RCT), thus its anti-atherogenic function. However, torcetrapib, a compound that increases plasma HDL-C levels, was unexpectedly associated with an increased cardiovascular mortality. The findings led to consider that HDL functionality and quality might be more relevant to CVD than the total circulating HDL quantity itself. Adherence to the Mediterranean diet is known to be associated with increased HDL-C and decreased risk of CVD. However, the mechanism by which this happens has been yet poorly investigated and the effect of nutrition on HDL functionality and quality needs further attention.